A MECHANISM OF ABSTRACTION FOR INDEPENDENT DEFINITION OF GAME’S PLATFORM ELEMENTS - Carlos Enrique Montenegro Marín; Juan Manuel Cueva Lovelle; Jordan Pascual Espada (Visión Electrónica, 2014)
This article is aimed at determining the feasibility of using a common mechanism to define the configuration in games for mobile devices. Such a configuration is intended to increase the level of abstraction up to a point where the definition of a platform game in XML format is made independent. This should then be read and deployed in an automatic way over any mobile platform.